2020
DOI: 10.21203/rs.3.rs-54067/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers to the Cervical Cancer Screening in the Northern Slovakia

Abstract: Background A barrier to screening is a specific attitude, opinion or state that prevents the patient from seeking preventive care. The aim of this study was to identify and compare barriers to cervical cancer screening (CCS) in Northern Slovakia between women seeking and not seeking CCS. Methods Data collection was performed in twenty gynaecological departments, each department sending data from five healthy women and five untreated women with cervical cancer. Women completed a validated and standardized que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…11 Furthermore, previous studies have shown that sociodemographic factors such as country of birth (eg, born in a foreign country), unemployment or lower socioeconomic status are associated with an increased likelihood of dismissing cancer screenings. 12,13 However, studies examining determinants of postponed cancer screenings are lacking in general -and in particular during the COVID-19 pandemic. The COVID-19 pandemic is accompanied by various challenges for the health and the health care system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, previous studies have shown that sociodemographic factors such as country of birth (eg, born in a foreign country), unemployment or lower socioeconomic status are associated with an increased likelihood of dismissing cancer screenings. 12,13 However, studies examining determinants of postponed cancer screenings are lacking in general -and in particular during the COVID-19 pandemic. The COVID-19 pandemic is accompanied by various challenges for the health and the health care system.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Furthermore, previous studies have shown that sociodemographic factors such as country of birth (eg, born in a foreign country), unemployment or lower socioeconomic status are associated with an increased likelihood of dismissing cancer screenings. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%